Global Citizenship Education: A Curricular Innovation in Social Sciences - Nicolás Aguilar-Forero; Diego Fernando Mendoza Torres; Ana María Velásquez; Daniel Felipe Espitia; Jennifer Ducón Pardey; Jana De Poorter (Universidad Autónoma de Madrid, 2019)
This study explores a curricular innovation in the social studies class of a public school in Bogota, Colombia, in order to integrate some of the Global Citizenship Education objectives in the curricula of tenth grade students. Through an action research project, we were able to reform the teacher's former plan of studies to enrich it with a global vision of the topics discussed. Results show how, through ludic and innovative strategies, students understand the differences among various government systems, and the sense of democratic participation. Likewise, through comparative exercises, they get to understand the complexity of armed conflict in Colombia, in dialogue with the processes of democratic transition that took place in other countries. Lastly, thanks to research activities about global social movements and to the use of portfolios, students analyze the motives and forms of action of those movements, and empathically identify themselves with the defense of human rights. Learned lessons for teachers interested in conducting similar innovations in their classrooms are highlighted.